Patient-Ventilator Synchronization During Non-invasive Ventilation: A Pilot Study of an Automated Analysis System - Letellier, Christophe; Lujan, Manel; Arnal, Jean-Michel; Carlucci, Annalisa; Chatwin, Michelle; Ergan, Begum; Kampelmacher, Mike; Storre, Jan Hendrik; Hart, Nicholas; Gonzalez-Bermejo, Jesus; Nava, Stefano (Frontiers in Medical Technology, 2021)
BACKGROUND: Patient-ventilator synchronization during noninvasive ventilation (NIV) can be assessed by visual inspection of flow and pressure waveforms but, it remains time consuming and there is a large inter-rater variability, even among expert physicians. SyncSmart™ software, developed by Breas Medical (Mölnycke, Sweden), provides automatic detection and scoring of patient-ventilator asynchrony to help physicians in their daily clinical practice. This study was designed to assess performance of the automatic scoring by the SyncSmart software using expert clinicians as reference in patients with chronic respiratory failure receiving NIV. METHODS: 9 patients, 20 minute data sets were analysed automatically by SyncSmart software and reviewed by 9 expert physicians who were asked to score auto-triggering (AT), double-triggering (DT), and ineffective efforts (IE). For each patient, the asynchrony index was computed by automatic scoring and each expert, respectively. Considering successively each expert scoring as a reference, sensitivity, specificity, positive predictive value (PPV), κ-coefficients, and agreement were calculated. RESULTS: The asynchrony index assessed by SyncSmart was not significantly different from the one assessed by the experts (18.9±17.7 versus 12.8±9.4, p = 0.07). When compared to an expert, the sensitivity and specificity provided by SyncSmart for AT, DT, and IE were significantly greater than those provided by an expert when compared to another expert. CONCLUSION: SyncSmart software is able to score asynchrony events within the inter-rater variability. When the respiratory rate is < 24 bpm, it therefore provides a reliable assessment of patient-ventilator asynchrony; AT is over detected otherwise.